2015
DOI: 10.1002/iid3.66
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the biosynthesis of platelets‐derived extracellular vesicles

Abstract: Platelet-derived extracellular vesicles (PEVs) are described as sub-cellular vesicles released into circulation upon platelets shear stress, activation, injury, or apoptosis. They are considered as universal biomarkers in a wide range of physiological and pathological processes. They are of tremendous significance for the prediction, diagnosis, and observation of the therapeutic success of many diseases. Understanding their biosynthesis and therefore functional properties would contribute to a better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…CD63 is a tetraspanin, which in numerous studies was shown to play a role in formation of various EVs including endothelial EVs [12, 38]. Moreover, it was demonstrated that CD63 (traditionally considered to be a sign of activated platelets [39]) should be detected on the majority of platelet-derived vesicles, which can be released only upon activation or death of platelets due to structural features of the platelet membrane [40, 41]. Thus, use of this marker allowed additional characterization of EVs released both from platelets and from endothelium cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD63 is a tetraspanin, which in numerous studies was shown to play a role in formation of various EVs including endothelial EVs [12, 38]. Moreover, it was demonstrated that CD63 (traditionally considered to be a sign of activated platelets [39]) should be detected on the majority of platelet-derived vesicles, which can be released only upon activation or death of platelets due to structural features of the platelet membrane [40, 41]. Thus, use of this marker allowed additional characterization of EVs released both from platelets and from endothelium cells.…”
Section: Discussionmentioning
confidence: 99%
“…The biomolecules carried by EVs, including proteins, nucleic acids and lipids, are reflective of the cell of origin 11 . Although the distinguishing characteristics of EVs in blood still remain unclear, some specific features have been identified, such as prostate-specific antigen on exosomes in urine from patients as markers of prostate cancer-derived EVs 12 , claudin on exosomes in peripheral blood as markers of ovarian cancer 13 , and several potential markers including CD31, CD41, CD42a, CD62p (P-selectin), platelet factor 4 (PF4) and glycoproteins IIb/IIIa (GPIIb/IIIa) as markers of platelet-derived EVs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are no definitive propositions for the use of plasma over sera for EV biomarker discovery. The process to separate serum from blood first requires blood coagulation, which causes platelet activation and leads to increased platelet-EV secretion [61]. Sera also comprises a higher proportion of particles larger than 200 nm, compared to plasma [62] and thus plasma was selected as the starting material to optimise our biomarker workflow.…”
Section: Discussionmentioning
confidence: 99%